Safety, pharmacokinetics, and pharmacodynamics of sofnobrutinib, a novel non‐covalent BTK inhibitor, in healthy subjects: First‐in‐human phase I study - Kyoko Miyamoto; Robert M. Miller; Christine Voors‐Pette; Jart A. F. Oosterhaven; Marieke van denDobbelsteen; Katsuhiro Mihara; Marian Geldof; Yuji Sato; Naomi Matsuda; Shirou Kirita; Masaaki Sawa; Akinori Arimura (Wiley, 2024)
Abstract Bruton's tyrosine kinase (BTK) is a potential therapeutic target for allergic and autoimmune diseases. This first‐in‐human phase I study evaluated safety, pharmacokinetic, and pharmacodynamic profiles of sofnobrutinib (formerly AS‐0871), a highly selective, orally available, non‐covalent BTK inhibitor, in healthy adult subjects. Single ascending doses (SAD; 5-900 mg) and multiple ascending doses (MAD; 50-300 mg twice daily [b.i.d.] for 14 days [morning dose only on Day 14]) of sofnobrutinib were tested. In the entire study, all adverse events (AEs) were mild or moderate, and no apparent dose‐proportional trend in severity or frequency was observed. No serious treatment‐emergent AEs, cardiac arrythmias, or bleeding‐related AEs were reported. In the SAD part, sofnobrutinib exhibited approximately dose‐dependent systemic exposures up to 900 mg with rapid absorption (median time to maximum concentration of 2.50-4.00 h) and gradual decline (mean half‐lives of 3.7-9.0 h). In the MAD part, sofnobrutinib showed low accumulation after multiple dosing (mean accumulation ratios of ≤1.54) and reached a steady state on ≤Day 7. Single dosing of sofnobrutinib rapidly and dose‐dependently suppressed basophil and B‐cell activations in ex vivo whole blood assays. Multiple dosing of sofnobrutinib achieved 50.8%-79.4%, 67.6%-93.6%, and 90.1%-98.0% inhibition of basophil activation during the dosing interval of 50, 150, and 300 mg b.i.d., respectively. Based on pharmacokinetic‐pharmacodynamic analysis, half‐maximal inhibitory concentration (IC50) of sofnobrutinib for basophil activation was 54.06 and 57.01 ng/mL in the SAD and MAD parts, respectively. Similarly, IC50 for B‐cell activation was 187.21 ng/mL. These data support further investigation of sofnobrutinib in allergic and autoimmune diseases.